2003
DOI: 10.1246/cl.2003.1114
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Gold Nanoplates by a Microwave-polyol Method

Abstract: Triangular, square, and hexagonal gold nanoplates with diameters of 30–90 nm have been prepared through a microwave-polyol method. These nanoplates gave new plasmon band of Au in the 550–800 nm region. It was concluded that nonthermal effect plays a significant role for the formation of Au nanoplates under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 4 publications
3
89
0
2
Order By: Relevance
“…2), broad surface plasmon bands of Au nanoparticles appear in 500-700 nm regions. It is known that a surface plasmon band of spherical Au nanoparticles appears in the 500-600 nm regions with a sharp peak at about 520 nm (Henglein, 1999;Pastoriza-Santos and Liz-Marzan, 2002;Malikova et al, 2002) while plasmon bands of polygonal Au nanoparticles are observed in the 550-800 nm region (Tsuji et al, 2003).…”
Section: Synthesis Of Au Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…2), broad surface plasmon bands of Au nanoparticles appear in 500-700 nm regions. It is known that a surface plasmon band of spherical Au nanoparticles appears in the 500-600 nm regions with a sharp peak at about 520 nm (Henglein, 1999;Pastoriza-Santos and Liz-Marzan, 2002;Malikova et al, 2002) while plasmon bands of polygonal Au nanoparticles are observed in the 550-800 nm region (Tsuji et al, 2003).…”
Section: Synthesis Of Au Nanoparticlesmentioning
confidence: 99%
“…In general, a mixture of reagent and polymer surfactant in Ethylene Glycol (EG) was heated in an oil bath for several hours and spherical nanoparticles were prepared. Recently Microwave (MW) heating has been coupled with the polyol method for rapid preparation of Au nanoparticles (Tsuji et al, 2003;. This study describes the preparation of various sizes and shapes of Au nanoparticles for mercury adsorption by using polyol method under MW heating.…”
Section: Introductionmentioning
confidence: 99%
“…The metal and semiconductor nanoparticles synthesis is an extending research area for the potential applications of nanoparticles and for the advancement of novel technologies [2,3]. The nanoparticles can be synthesized by different methods (physical, chemical, and biological) and by using different substrates (pure compounds, microorganism, and plant extract) [4,5]. The chemical approach is robustly scaled for the large-scale production of nanoparticles of tunable shape and size by using different synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle synthesis using physical and chemical processes are routinely utilized to synthesize metal nanoparticles, which allow one to obtain particles with the desired characteristics (Tsuji et al, 2003). However, both these methods are usually expensive, laborintensive, and are potentially hazardous to the environment and living organisms (Narayana and Sakthivel, 2010).…”
Section: Introductionmentioning
confidence: 99%